Climate risk and low-carbon policies: implications for sports economics and global events - Siyu Fu; Chen Kong (Frontiers in Environmental Science)
IntroductionAs global climate change accelerates, its multifaceted impacts are becoming increasingly evident in the sports industry, especially in the context of large-scale international sporting events. Rising temperatures, extreme weather events, and the tightening of environmental regulations are placing unprecedented operational and financial pressures on sports organizations. Meanwhile, the global push toward carbon neutrality compels event organizers to adopt sustainable practices across all facets of planning, infrastructure, and athlete management. However, traditional models in sports economics remain largely inadequate to address these emerging challenges, as they are primarily designed to optimize short-term revenue and performance outcomes, neglecting environmental and policy dimensions.MethodsTo address this gap, this paper proposes an integrated analytical framework that brings together the Dynamic Athlete Valuation Model (DAVM) and the Integrated Competitive Strategy Framework (ICSF). DAVM introduces a dynamic, data-driven approach to athlete valuation, incorporating temporal performance metrics, market conditions, and external factors such as sponsorship and media influence. ICSF, on the other hand, leverages game theory and optimization algorithms to enhance decision-making in areas such as resource allocation, salary cap management, and sustainability-oriented strategic planning.ResultsEmpirical results from multiple datasets and experiments confirm that the integration of climate risk and low-carbon policy variables significantly improves the predictive accuracy and resilience of economic planning in the sports sector.DiscussionThis research provides theoretical advancements and practical insights for policymakers, sports managers, and investors seeking to navigate the complex interplay between sustainability and profitability in a rapidly changing global environment.